Study on the Establishment of Efficient Leaf Regeneration System in ‘Yuluxiang’ Pear - Xiaohua Cheng; Weilong Zhang; Yarui Wei; Yuxing Zhang (Horticulturae)
The ‘Yuluxiang’ pear is a key cultivated variety in China, celebrated for its high quality. However, it exhibits a low leaf regeneration frequency of only 35.0%, which hinders its transgenic breeding process. To establish an efficient regeneration system, we utilized tissue culture seedlings of the ‘Yuluxiang’ pear and investigated various factors influencing leaf regeneration: plant growth regulators, natural organic materials, leaf wounding and positioning methods, duration of dark culture, ages and lines of plantlets, as well as culture containers. Our results indicated that the optimal medium for leaf regeneration consisted of MS supplemented with 6-BA (6-Benzyl Aminopurine) 1.5 mg/L, NAA (α-Naphthalene acetic acid) 0.4 mg/L along with 10% (v/v) coconut water. Suitable wounding involved ensuring no damage to leaves while placing the abaxial side facing down on the medium; the ideal duration for dark culture was determined to be 21 days; optimal plantlet age was found to be 20 days; both plantlet line 1 and line 2 demonstrated effectiveness; triangle bottles were identified as appropriate culture containers. In summary, we successfully established an efficient leaf regeneration system for the ‘Yuluxiang’ pear that achieved a maximum regeneration frequency of 96.70% with an average bud number of 5.15 per explant. This system also proved effective for the ‘Qiuyue’ pear, yielding a regeneration frequency of 88.89% and an average bud number of 3.44 per explant. After investigating the germination methods of 200 leaves from this screened leaf regeneration system of ‘Yuluxiang’, it was found that there were both direct and indirect regeneration methods, and the germination rate of direct and indirect regeneration was 68.00% and 70.50%, respectively. Therefore, this study also laid a solid foundation for the future genetic transformation of ‘Yuluxiang’ pear.